Obesity alters ovarian folliculogenesis through disrupted angiogenesis from increased IL-10 production - Po-Kai Yang; Chia-Hung Chou; Chu-Chun Huang; Wen-Fen Wen; Hsin-Fu Chen; Chia-Tung Shun; Hong-Nerng Ho; Mei-Jou Chen (Elsevier, 2021)
Objective: Obesity has been reported to have a modulatory effect on the ovulatory functions of patients with polycystic ovary syndrome. The role of adipokines in this obesity-associated ovulatory disturbance has not been extensively explored. In this study, the relationships between obesity, adipokine production from visceral fat, and ovarian folliculogenesis were explored in a mice model of induced obesity. Methods: Obesity was induced in female C57BL/6 mice fed ad libitum with high-fat feed and fructose water for 4 weeks. Follicular developments in the ovaries were assessed by histopathology in these diet-induced obese mice. Changes in adipokine expression in the peri-ovarian adipose tissues were screened with an adipokine array. The adipokine with the most significant increase over time was identified. The functions of the adipokine in angiogenic processes were evaluated in a cell model of endothelial proliferation. The in vivo effects of neutralizing this adipokine using specific antibodies were assessed in the same obesity model. Results: A high-fat and fructose diet induced an accumulation of early ovarian follicles and a reduction in mature follicles and corpus lutea. The number of microvessels in the early follicles also decreased. The adipokine protein array of the peri-ovarian adipose tissues identified a progressive increase in IL-10 expression with the duration of the obesogenic diet. In vitro experiments in the endothelial cell model confirmed IL-10 as a disrupter of VEGF-induced angiogenesis. Administration of anti-IL-10 antibodies prevented the histopathological changes induced by the obesogenic diet and further highlighted the role of IL-10 in disrupting folliculogenesis. Conclusions: Obesity may disrupt normal folliculogenesis through increased production of IL-10 in visceral fats. This relationship may help clarify the reported association between obesity and ovulatory dysfunction, which has been found in patients with polycystic ovary syndrome. However, the duration of this study was short, which limited conclusions on the long-term reproductive outcomes.